Current and Future Direct-Acting Antivirals Against COVID-19 - Chan, Shiu-Wan (Frontiers in Microbiology, 2020)
The coronavirus disease of 2019 (COVID-19) has caused an unprecedented global crisis. The aetiological agent is a new virus called the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). As of 25 July, 2020 there have been 15.5 million confirmed cases with a mortality rate of 4% globally. With the lack of a vaccine and effective treatments, the race is on to find a cure for the virus infection using specific anti-virals. The viral RNA-dependent RNA polymerase, proteases, spike protein-host angiotensin-converting enzyme 2 binding and fusion have presented as attractive targets for pan-coronavirus and broad spectrum direct-acting antivirals. This review presents a perspective on current re-purposing treatments and future direct-acting antivirals.